Short-Term Nitrate Uptake Rates for Soilless Culture: Seasonal Empirical Relationships for Rose Crop Production - Roca, Dolors; Belda, R. M.; Calatayud, Ángeles; Gorbe, Elisa; Martínez, Pedro F. (2017)
Simplified versions of Penman-Monteith model can be applied for the water and climate management in greenhouse culture. They relate plant transpiration flux to solar radiation (Gin), leaf area and air vapour pressure deficit, VPD. Integrating the model-based algorithm in the greenhouse control system allows for a precise control of water supply. Fertigation systems such as those used for rose crops in greenhouses, allow implementing a model for plant nitrate uptake based on water uptake. Although for large periods of time, e.g. weeks or months, both water uptake and nitrate uptake are found to correlate positively, a model would prove useful for soilless culture if it were successful in predicting nitrate uptake at shorter periods. Nitrate and water uptake rates by a rose (Rosa x hybrida cv. Dallas) crop were measured hourly for 24 hour periods along the four seasons. Means of nitrate uptake rate (NUR, mmol NO(3)(-) h(-1) p(-1)) in the spring and autumn seasons were some 32% larger than in summer and winter. However, in summer and autumn the daily nitrate uptake efficiency, expressed as NUR per unit of plant dry weight (mu mol NO(3)(-) g(-1) p(-1)), was the largest of the year. This was likely due to the unbalanced dry matter distribution between root and shoot following the late spring pruning and to the subsequent nutritional response aiming to the recovery of the plant. Empirical models for NUR were developed by means of analysis of stepwise multiple regression. The regressor variables considered for the model were water uptake rate (WUR), Gin (simultaneously measured to nitrate uptake registration or accumulated in the previous 4 (Gin4), 8 (Gin8) and 12 (Gin12) hours), air temperature (airT) and VPD, both from inside the greenhouse, and temperature of the nutrient solution surrounding the root system (rootT). Three highly significant regression 2 models were obtained: NUR was related to WUR and rootT 2 in the summer (r(2)=0.81), to WUR in autumn (r(2)=0.85) and to VPD in spring (r(2)=0.85). Night root temperature is highest in the summer. This high root-zone temperature may pose a limiting condition for the nitrate transporters in the root as has been reported in the literature. VPD in spring is the lowest for the three seasons with highest significant models, which suggests that the crop can be in a better condition for a favourable water balance status. Maybe for this reason VPD is integrating other effects and results as the prevailing factor selected by the model in the spring.